The Obstacles of the Effective Organizing of Strategic Think Tanks - Ashraf Lajevardi (مطالعات مدیریت راهبردی, 2010)
Think thanks play an essential role in developing general policies and increasing the related capacities. The way of organizing them is among the determinants of this role. Therefore, it is necessary to revise their organization regularly in order to recognize the proper organizing relative to the think tanks' goals and other unstable environmental, economic, social conditions. In each revision the barriers leading to reduction of think tanks efficiency will be discovered and overcome. In this way their competition and attempts will increase in order to improve public policy's capacity. In this regard we use the literature, extracted its theoretical principles and distributed among the universities' scientific members in the form of a questionnaire. The results achieve by the Freidman and T.test revealed that some barriers have the most effects on the organizing think tanks and their effectiveness. On the other, hand three factors have not been assumed as effective barriers in organizing think tanks. They have been considered in discussion and conclusion. Finally, the research's suggestions have been offered.